Conventional and advanced borehole investigation methods for inaccessible underground voids - Pak, M.; Preston, R.P.; Groccia, C.; Taylor, J. (UMT 2017: Proceedings of the First International Conference on Underground Mining Technology, 2017)
Determining mitigation and remediation options for underground voids, such as those associated with active or abandoned underground mine development openings and mined out stopes, can be difficult due to limitations of safe access, flooding, and void geometry uncertainty. Recent advances and improved technology associated with borehole investigation methods are making the job easier and more cost-effective. Specialised cameras used to conduct investigative surveys through boreholes have been applied to solve such problems for many years. Recent advances in electronics, digital cameras, and low-cost production have allowed for a wider use of the technology. Other borehole-based tools such as cavity monitoring systems/LIDAR for dry voids, and borehole-based sonar for flooded voids can be used in conjunction with borehole camera surveying to maximise the data that can be collected through expensive boreholes. These methods greatly reduce uncertainty by providing high-resolution scaled models of the intersected void. The ability to collect an enhanced dataset for a small incremental cost, relative to the cost of drilling, improves the cost benefit by reducing uncertainty. The benefits and challenges associated with each borehole investigation method, as well as considerations for optimising the quality of data collected, are discussed using examples from Giant Mine in the Northwest Territories, Canada and the Kam Kotia Mine and the Mine N claim in Ontario, Canada.